Phenomenology Is A Humanism: Husserl’s Hermeneutical- Historical Struggle to Determine the Genuine Meaning of Human Existence in "The Crisis of the European Sciencies and Transcendental Phenomenology" - Hefferman, George (Investigaciones Fenomenológicas, 2021)
In The Crisis of the European Sciences and Transcendental Phenomenology (1936), Husserl expands his philosophical horizon to include the question about the genuine meaning of human existence. Understanding the crisis of the European sciences as a symptom of the crisis of European philosophy and as an expression of the life-crisis of European humanity, and interpreting European science, philosophy, and humanity as representative of their global-historical counterparts, Husserl argues that the life-crisis of European humanity is reflective of the critical condition of global-historical humanity. The crisis of “European” life emerges as a crisis of human existence, and Husserl’s phenomenology unfolds as a search for an answer to the question not only about the sense of the life-world but also about the meaning of human life. Thus phenomenology, as care for humanity, shares with existentialism, as a humanism in the broadest sense, the conviction that human beings live in a world not in which life makes sense, but in which they must make sense of life. Accordingly, the genuine essence of human existence is not passively “given” but actively “taken,” since it involves an entelechy that constitutes itself in an evolutionary achievement, and it is the evidentiary result of an existential struggle for meaning against annihilating forms of meaninglessness, namely, irrationalism, positivism, and skepticism. This paper examines Husserl’s hermeneutical-historical approach to the question about the meaning of human existence and suggests an understanding of phenomenology as a form of humanism, and perhaps even as a unique kind of “existentialism,” that is, an ethical philosophy that takes absolute moral responsibility for the presuppositionless application of reason to life. En La crisis e las ciencias europeas y la fenomenología trascendental (1936), Husserl expande su horizonte filosófico a fin de incluir en él la pregunta por el auténtico sentido de la existencia humana. Al entender la crisis de las ciencias europeas como un síntoma de la crisis de la filosofía europea y como una expresión de la crisis vital de la humanidad europea, y al interpretar la ciencia, la filosofía y la humanidad europeas como representativas de sus contrapartes históricas y globales, Husserl argumenta que la crisis vital de la humanidad europea refleja la condición crítica en que se encuentra la humanidad en perspectiva histórica global. La crisis de la vida “europea” emerge como una crisis de la existencia humana, y la fenomenología de Husserl se despliega como la búsqueda de una respuesta a la cuestión no sólo del sentido del mundo de la vida, sino también del significado de la vida humana. La fe-nomenología, como cuidado de la humanidad, comparte con el existencialismo, entendido como un humanismo en el sentido más amplio, la convicción de que los seres humanos viven en un mundo en el cual no es que la vida tenga sentido sino que ellos deben dar sentido a la vida. En consonancia, la auténtica esencia de la existencia humana no está pasivamente “dada” sino que es activamente “tomada”, ya que ella envuelve una entelequia que se constituye en una realización evolutiva, y que es el resultado evidenciador de un combate existencial por el significado contra las formas de sinsentido que son aniquiladoras, a saber: irracionalismo, positivismo y escepticismo. Este ensayo examina la aproximación histórico-hermenéutica de Husserl a la cuestión del significado de la existencia humana, y sugiere una comprensión de la fenomenología como una forma de humanismo, y quizá incluso como un tipo único de existencialismo; esto es, como una filosofía ética que asume una responsabilidad moral absoluta en la aplicación sin presupuestos de la razón a la vida.